Intercultural Communications. Roma-Polish Relationships in School Environment — Early Education Stage - Grzelak, Eliza; Grzelak-Piaskowska, Joanna (Poznańskie Towarzystwo Przyjaciół Nauk, 2013)
The authors of the article were concerned with the intercultural communal communication in a school environment. The aim of the research was to determine the barriers which impede achieving a communal goal — the increase of educational competence among Roma pupils, as well as demonstrating how the communal goals may be attained in within the boundaries of community delimited by the convention and curriculum. Finally, the authors presented the techniques of building favourable relationships at the juncture of cultures, while relying on the norms and communication strategies developed by a given community.
Keywords: intercultural communication; education of the Roma; communication community; discourse community; assimilation; integration; multiculturalism